Drivetrain influence on the lead-lag modes of hingeless helicopter rotors - Weiss, F.; Kessler, C. (My University, 2018)
Structural couplings between the 2exible main rotor and the 2exible drivetrain of the Bo105 helicopter are investigated by numerical simulation. For this purpose, the rotor hub constraint ? = const. is dropped and a drivetrain model, consisting of discrete inertia elements and intermediate 2exible elements, is connected to the hub. By use of the multibody-software SIMPACK, the coupled rotor-drivetrain system is linearized and the Eigenmodes are compared to those obtained with a constrained rotor hub. The drivetrain has a signi1cant in2uence on the shapes and Eigenfrequencies of the collective lead-lag modes. While the 1rst collective lead-lag Eigenfrequency is raised by the 1nite drivetrain inertia, the second is lowered due to drivetrain 2exibility. To assess the in2uence of modeling inaccuracies on the observed couplings, the study is complemented by a sensitivity analysis. Rotor blade mass axis offset, blade pitch (causing elastic coupling) and blade precone angle have only weak in2uence on the coupled modes. In contrast, variations of drivetrain inertia and stiffness strongly affect the Eigenfrequencies of the coupled rotor-drivetrain modes.